2009
DOI: 10.1007/s11524-009-9345-8
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Violence and its Association with Mothers’ Health: Assessing the Relative Importance of Perceived Safety and Exposure to Violence

Abstract: This paper presents a cross-sectional study examining the influence of neighborhood violence on multiple aspects of mothers' health. While the influence of neighborhood violence on health is important to understand for all populations, mothers are especially important as they play a key role in protecting their children from the consequences of violence. Three hundred and ninety-two Baltimore City mothers of children 5 years and younger completed a self-administered survey that included questions about percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 42 publications
(58 reference statements)
2
53
0
Order By: Relevance
“…These findings are consistent with previous studies that reported an association between short sleep duration and low neighborhood safety. [10][11][12][13][14][15][20][21][22] These prior studies however, relied on self-reported sleep duration, raising concern that the associations might reflect known systematic biases in the accuracy of self-report, rather than an actual effect on sleep per se. Our results demonstrate that the perception that one lives in an unsafe neighborhood is associated with an objective measure of short sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with previous studies that reported an association between short sleep duration and low neighborhood safety. [10][11][12][13][14][15][20][21][22] These prior studies however, relied on self-reported sleep duration, raising concern that the associations might reflect known systematic biases in the accuracy of self-report, rather than an actual effect on sleep per se. Our results demonstrate that the perception that one lives in an unsafe neighborhood is associated with an objective measure of short sleep.…”
Section: Discussionmentioning
confidence: 99%
“…10 This suggests that effects of neighborhood characteristics on sleep may represent one pathway by which neighborhood environment has an impact on health outcomes. Exposure to violence and crime and feeling unsafe in one's neighborhood have been associated with reductions in both sleep duration [11][12][13] and sleep quality, 10,[12][13][14] and worse insomnia symptoms. 15 Similarly, increased noise in the neighborhood has been associated with higher prevalence of self-reported sleep disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Other items were based on existing validated survey items on income security, 37 food security, 38 and neighborhood safety. 39 Likert-scale response options were as follows: 1 = "not at all stressful," 2 = "a little bit stressful," 3 = "moderately stressful," 4 = "very stressful, " 5 = "extremely stressful," and 0 "issue listed is not applicable to my family." Each social need was coded in a binary format as either 0 (if "not at all stressful" or "not applicable to my family") or 1 (if "a little stressful" to "extremely stressful") to indicate a positive disclosure.…”
Section: Psychosocial Needs Assessmentmentioning
confidence: 99%
“…This comprehensive approach emphasizes the importance of integrating mental health into HIA methodology (Quigley et al 2006). Additionally, mental health plays a critical role in mediating the relationship between social conditions and physical health outcomes (Leventhal and Brooks-Gunn 2000, Stafford et al 2007, Curry et al 2008, Echeverria et al 2008, Collins et al 2009, Johnson et al 2009, O'Campo et al 2009, Raphael 2009, Roman et al 2009, Geronimus et al 2010, Mair et al 2010, Matthews et al 2010.…”
Section: Mental Health Impact Assessmentmentioning
confidence: 99%